Memory-access-aware data structure transformations for embedded software with dynamic data accesses. - Daylight, E.G (IEEE Transactions on VLSI systems)
Embedded systems are evolving from traditional, stand-alone devices to devices that participate in Internet activity. The days of simple, manifest embedded software [e.g. a simple finite-impulse response (FIR) algorithm on a digital signal processor (DSP] are over. Complex, nonmanifest code, executed on a variety of embedded platforms in a distributed manner, characterizes next generation embedded software. One dominant niche, which we concentrate on, is embedded, multimedia software. The need is present to map large scale, dynamic, multimedia software onto an embedded system in a systematic and highly optimized manner. The objective of this paper is to introduce high-level, systematically applicable, data structure transformations and to show in detail the practical feasibility of our optimizations on three real-life multimedia case studies. We derive Pareto tradeoff points in terms of accesses versus memory footprint and obtain significant gains in execution time and power consumption with respect to the initial implementation choices. Our approach is a first step to systematically applying high-level data structure transformations in the context of memory-efficient and low-power multimedia systems.